Evaluation of Story and Storytelling Curriculum in Preschool with Emphasis on Presenting Desirable Pattern - roointan, Zeinab; Jalalvandi, Mahnaz; Nateghi, Faeze (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this study was to investigate the storytelling and storytelling curriculum in preschool and presenting a favorable role model.Methodology: This study was a descriptive survey. The research method was mixed method. Due to the exploratory nature of the research and the way in which the data were collected and arranged, (firstly qualitatively and then quantitatively) this research has been classified into successive exploration plans. The qualitative part uses the documentary method and the quantitative part uses the descriptive survey method. The statistical environment of the study consisted of all books, articles, theses, and printed and electronic texts related to the subject. Structured interviews were used to collect data and purposeful sampling was used.Findings: The results of content analysis in qualitative part including open coding and axial coding showed that ratings of storytelling and storytelling components in preschool curriculum were from the strongest to the weakest, respectively: cognitive goals, attitude goals, skill goals, Evaluation, content, teaching and learning methods. The results of t-test showed that the mean of obtained sample (3.70) was higher than the mean of community (3)Conclusion: The results showed that storytelling and storytelling can have a significant role in the curriculum and motivate students to be more motivated and motivated to study formal and higher education. He should have a positive and positive impression of school and school.